How we use patient encounter data for reflective learning in family medicine training. (3rd October 2015) - Morgan, Simon; Henderson, Kim; Tapley, Amanda; Scott, John; van Driel, Mieke; Thomson, Allison; Spike, Neil; McArthur, Lawrie; Presser, Jenny; Magin, Parker
Abstract: Introduction : Consulting with patients is the core learning activity of Australian family medicine (general practice/GP) training, providing a rich source of reflective learning for trainees. We have developed a reflective learning program for postgraduate vocational trainees based on clinical encounters. Methods : The Registrar Clinical Encounters in Training (ReCEnT) program is an educational program documenting GP trainees' consultations in five Australian GP training providers. Trainees record patient demographics, consultation details, problems managed, management practices and educational factors from sixty consecutive consultations per six-month training term. Trainees receive a detailed feedback report comparing individual data to aggregated trainee data and national GP data. Results : The patient encounter system provides multiple opportunities for reflective learning across a number of domains of exposure and practice. Reflection can occur during completion of the encounter form; as self-reflection on the feedback report; as facilitated reflection with the GP trainer and medical educator; and as part of integration of data into teaching. We have identified areas for further development, including enhancing the reflective skills of trainees and trainers. Conclusion : The ReCEnT patient encounter program provides a rich platform for reflective learning for vocational trainees and supports development of skills in lifelong learning.